Situational Analysis of Institutional and Safe Delivery: A Study in Rural Deoria (Uttar Pradesh) - Singh, Kanchan; Singh, Jagadish (National Geographical Journal of India, 2022)
Maternal and child health issues continue to be at forefront among national and global health policies. In developing countries maternal and infant mortality rates are quite high and to reduce this, institutional and safe delivery can contribute significantly. India also registered high maternal and infant mortality rates. To promote institutional deliveries and reduce the risk of maternal and infant deaths, the Government of India has initiated Maternal and Child Health (MCH) programme and also Janani Suraksha Yojna (JSY) under National Rural Health Mission (NRHM) but could achieve only a partial success The present study is an exploratory attempt to analyse the factors which affect to the institutional delivery in rural areas of Deoria district. Deoria is one of the backward districts of Eastern Uttar Pradesh where 27,12,650 persons inhabit over 2,538 km of area. In the district 90.1 per cent population reside in rural areas as per 2001 Census. The study area has registered 71 infant deaths per 1,000 live births and 517 mother deaths on 100,000 live births in 2000-01. To examine the state of institutional and safe deliveries a total of 516 ever married respondents belonging to sixteen development blocks have been interviewed during 2007-08 following Purposive Random Sampling technique. The result portrays that in the study area delivery at home (66.3%) is almost twice as compared to the institutional delivery (33.7 %). Only 37.2 per cent births were attended by trained health professionals. The socio-economic determinants such as caste, education, age at marriage and income have widely affected the utilization of institutional and safe delivery in rural areas of the study area.